The Teaching of English by Using Telegram Application: A Case Study at SMKN (Vocational High School) 4 Malang - Mizan Yushril Rahmatullah Faqih Putra; Dian Inayati (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
This study aims to describe the implementation of Telegram application as a teaching media in teaching English and to know students’ perceptions toward this implementation. Using case study as research design, the teacher who used Telegram as teaching media in English teaching and 2 students who are taught by this teaching media were being participants in this qualitative study. The observation checklist form adapted from Lubis (2018) and the interview guidelines adapted from Chorida (2017) was used to gain the data. To reach the objective of the study, the researcher conducted online observation and interviews with those participants. The finding shows that the implementation of Telegram at SMKN 4 Malang can give positive impact in English language teaching. The use of Telegram facilitates students to autonomously learn. It is due to all of the materials needed by students are already provided with clear instructions by the English teacher in one of its features called Bot API. Related to the student responses in using Telegram application, students are pretty attractive to use this Telegram application as the teaching media. Therefore, it is suggested to English teachers to implement Telegram application as one of teaching media in delivering materials.